Nordic skiing - Labrecque, Ellen (Labrecque, Ellen. Global citizens: Olympic sports., 2018)
Explores the history of Nordic skiing as an Olympic sport. Highlights skiers from around the world, the popularity of the sport, and its economics. Includes resources for further information, a glossary, and color photographs.